Comparison of the magnetic anisotropy and spin relaxation phenomenon of dinuclear terbium(III) phthalocyaninato single-molecule magnets using the geometric spin arrangement - Morita, Takaumi; Damjanović, Marko; Enders, Markus (Journal of the American Chemical Society, 2018)
Herein we report the synthesis and characterization of a dinuclear TbIII single-molecule magnet (SMM) with two [TbPc2]0 units connected via a fused-phthalocyaninato ligand. The stable and robust complex [(obPc)Tb(Fused-Pc)Tb(obPc)] (1) was characterized by using synchrotron radiation measurements and other spectroscopic techniques (ESI-MS, FT-IR, UV). The magnetic couplings between the TbIII ions and the two π radicals present in 1 were explored by means of density functional theory (DFT). Direct and alternating current magnetic susceptibility measurements were conducted on magnetically diluted and nondiluted samples of 1, indicating this compound to be an SMM with improved properties compared to those of the well-known [TbPc2]−/0/+ and the axially symmetric dinuclear TbIII phthalocyaninato triple-decker complex (Tb2(obPc)3). Assuming that the probability of quantum tunneling of the magnetization (QTM) occurring in one TbPc2 unit is PQTM, the probability of QTM simultaneously occurring in 1 is PQTM2, meaning that QTM is effectively suppressed. Furthermore, nondiluted samples of 1 underwent slow magnetic relaxation times (τ ≈ 1000 s at 0.1 K), and the blocking temperature (TB) was determined to be ca. 16 K with an energy barrier for spin reversal (Ueff) of 588 cm-1 (847 K) due to D4d geometry and weak inter- and intramolecular magnetic interactions as an exchange bias (Hbias), reducing QTM. Four hyperfine steps were observed by micro-SQUID measurement. Furthermore, solution NMR measurements (one-dimensional, two-dimensional, and dynamic) were done on 1, which led to the determination of the high rotation barrier (83 ± 10 kJ/mol) of the obPc ligand. A comparison with previously reported TbIII triple-decker compounds shows that ambient temperature NMR measurements can indicate improvements in the design of coordination environments for SMMs. A large Ueff causes strong uniaxial magnetic anisotropy in 1, leading to a χax value (1.39 × 10-30 m3) that is larger than that for Tb2(obPc)3 (0.86 × 10-30 m3). Controlling the coordination environment and spin arrangement is an effective technique for suppressing QTM in TbPc2-based SMMs.
Gesehen am 10.04.2019